Examining the role of counsellors on eating disorders in Ghana - Joseph, Adu (Research Journal in Advanced Social Sciences, 2022)
This study aimed at analysing effects of eating disorder associated with humankind, with close reference to Atebubu as the case study. The study further examined the counsellors’ roles to mitigate these effects. The study adopted qualitative design because the focus was not only to compare the frequencies but also simple percentages. The analysis took into consideration fifty (50) respondents as the population sample with a balanced gender distribution of twenty-five (25) women and twenty-five (25) males. The purposive sampling technique was employed to elicit essential information for the investigation. Unstructured interviews and observation were the data collection instruments. It was identified that counsellors as agents of change in human lives should effectively counsel their clients on eating disorders. It was also discovered that, eating disorders dragged many individuals into health-related diseases and eventually, disowned their lives. Finally, it was realized that the effects of eating disorders brought about complicated diseases and life-threatening issues. Since life is essential commodity, this study recommend that populace should know when, where and what to eat to ensure good health. It was very insightful for this study to empower individuals to realize the awareness of the effects of eating disorders and its repercussion thereof.